2015
DOI: 10.11604/pamj.2015.20.253.2441
|View full text |Cite
|
Sign up to set email alerts
|

Malignant skin lesions in Oshogbo, Nigeria

Abstract: IntroductionThe aim of this study is to retrospectively assess the prevalence of some of skin malignancies in our environment and to provide a data base for creating awareness for prevention and early detection of the diseases in order to reduce morbidity and mortality associated with these skin lesions in our environment.MethodsThis is a retrospective study of all histologically diagnosed malignant skin lesions which presented at Ladoke Akintola University of Technology Teaching Hospital Osogbo Osun State bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…They are histological varieties with different clinical and prognostic expressions. The high prevalence of squamous cell carcinomas and melanoma in blacks unlike basal cell carcinomas among whites was reported by several studies [4] [5] [6]. In our context, skin cancers are of late diagnosis.…”
Section: Introductionsupporting
confidence: 54%
“…They are histological varieties with different clinical and prognostic expressions. The high prevalence of squamous cell carcinomas and melanoma in blacks unlike basal cell carcinomas among whites was reported by several studies [4] [5] [6]. In our context, skin cancers are of late diagnosis.…”
Section: Introductionsupporting
confidence: 54%
“…This higher prevalence may be due to the inclusion of biopsied cases only and therefore suggests the prevalence of skin cancer among skin biopsy specimen while excluding a large population of cases whose lesions were not biopsied. The most frequently observed primary skin cancer was squamous cell carcinoma, and it occurs at a frequency of 33.3% and at a mean age of 39.3 years This is however in contrast with the review of biopsy specimen at other Centre where melanoma was found to be most frequent (6,7).…”
Section: Discussionmentioning
confidence: 80%
“…The prevalence of skin cancers have previously been reported in some centres in Ni-geria. A prevalence of 5.5% was reported in Osogbo, whereas a prevalence of 27% was reported in Benin (6,7). While the incidence of skin cancers may still be higher in the Caucasians, an alteration in the ratio of the incidence as well as in the prevalence may require verification.…”
Section: Introductionmentioning
confidence: 97%
“…Noneless the 'barefoot' notion and of traumas as part of the disease history allowed in their cohort retrieved PPMM in farmers with a tendency to walk barefoot in their farm [9,10]. To note that 81,7% of the cases we observed, the lesion localized in the pressure point of the extremities, sole and heel, which explain the pressure exercised at that level associated with a reduced melanin level in that region.…”
Section: Discussionmentioning
confidence: 96%